Digital Transformation and Bank Performance: Exploring the Relationship in the Nepalese Banking Sector - Kandel, Arjun Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the relationship between digital transformation and the banking sector of Nepal, analyzing its association with operational efficiency, customer experience, and financial inclusion. Through a qualitative and analytical approach based on secondary data, the research evaluates digital adoption trends and perceived outcomes across major Nepalese banks, including private sector leaders like Standard Chartered Bank Nepal, Nabil Bank, and NMB Bank, as well as government-owned institutions such as Nepal Bank Limited and Rastriya Banijya Bank. There are significant advancements in digital banking services, including mobile banking, AI-driven platforms, and blockchain-based payment systems, which have enhanced transaction speed, reduced costs, and expanded financial access. However, challenges remain, including disparities between private and public banks, cybersecurity risks, and rural-urban digital divides. The study shows the need for regulatory reforms, infrastructure development, and digital literacy programs to ensure inclusive growth. The paper concludes with strategic recommendations for policymakers and financial institutions to accelerate the digital banking evolution of Nepal while mitigating risks.